2021
DOI: 10.1097/mpa.0000000000001930
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatogenic Diabetes, 2 Onset Forms and Lack of Metabolic Syndrome Components Differentiate It From Type 2 Diabetes

Abstract: Objectives: We compared pancreatogenic (DM3c) and type 2 diabetes mellitus. Methods: We compared age-, sex-, and diabetes mellitus duration-matched DM3c cases (n = 142) and type 2 diabetes mellitus (n = 142). Pancreatogenic diabetes was considered when it appeared after the diagnosis of pancreatitis or after pancreatic surgery.Results: Pancreatogenic diabetes presented lower body mass index (BMI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Pancreatogenic diabetes was characterized by a lower body mass index (BMI), required more insulin, had more episodes of hypoglycemia, but had lower rates of dyslipidemia and hypertension. It was found that T3cDM is characterized by a low BMI and the absence of elements of the metabolic syndrome [ 37 ].…”
Section: The Type 3c Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatogenic diabetes was characterized by a lower body mass index (BMI), required more insulin, had more episodes of hypoglycemia, but had lower rates of dyslipidemia and hypertension. It was found that T3cDM is characterized by a low BMI and the absence of elements of the metabolic syndrome [ 37 ].…”
Section: The Type 3c Diabetes Mellitusmentioning
confidence: 99%
“…T3cDM is associated with an incidence ranging from 25% to 80% with chronic pancreatitis [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The risk of diabetes in patients with chronic pancreatitis increases with the duration of the disease and with the severity of damage to the pancreas, especially in the early form of pancreatic calcifications.…”
Section: The Type 3c Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…A szekunder diabetes ezen speciális formája különösen aluldiagnosztizált betegség. Ennek oka, hogy általában nem kísérik sem a T1DM speciális tünetei, sem a T2DM-et is magában foglaló metabolikus szindróma általános szimptómái [45]. Valójában az összes cukorbetegség kb.…”
Section: Pancreatogen Diabetes Mint a Másodlagos Cukorbetegség Protot...unclassified
“…While T1DM is autoimmune-mediated and beta cell specific [6], T3cDM clinical presentation can be heterogeneous, exhibiting several conditions marked by varying levels of endocrine and exocrine impairments [7]. Likewise, studies indicate that patients with T3cDM have a reduced body mass index and are devoid of features linked to the metabolic syndrome associated with T2DM [16]. According to a study that included age-and sex-matched cohorts, individuals with post-pancreatitis DM have a higher risk of hospitalization and mortality compared to those with T2DM [17].…”
Section: Introductionmentioning
confidence: 99%